IDENTIFICATION OF MYOSTATIN GENE c.960delG LOCUS POLYMORPHISM IN INDONESIAN LOCAL SHEEP BY USING PCR-SSCP METHOD - Sumantri, C.; Jakaria, J.; Yamin, M.; Nuraini, H.; Andreas, E. (Diponegoro University, 2011)
Myostatin (MSTN) is a protein inhibit muscle growth. This protein is a member of a superfamily ofmolecules called transforming growth factors beta (TGF-b). Deletion in c.960delG (1-bp deletion atposition 960) disrupts the reading frame from amino acid (aa) position 320 to ending in a premature stopcodon in aa position 359 have been found in Norwegian White Sheep. This deletion in the myostatingene is responsible to increase muscle mass, also known as 'double muscling', in sheep. The purpose ofthis study was to identify the polymorphism of myostatin gene in c.960delG locus of local sheep inIndonesia. The 832 DNA sampels from sheep were collected from 13 populations belonging to thePriangan (86), Javanese Thin Tail (389 i.e. Jonggol, Banjar, Ciomas), Javanese Fat Tail (94), West NusaTenggara (136), Rote Island/East Nusa Tenggara (35), Kisar Island/Southwest Maluku (22),Donggala/South East Celebes (45) and Batur cross breed/Wonosobo, Central Java (25). A gene fragmentof MSTN c.960delG length 299 bp was successfully amplified by using the technique of PCR(polymerase chain reaction) and genotyped by SSCP (single strand conformation polymorphism). Theresult showed no polymorphism in this gene. All sheep tested had G/G genotype for c.960delG locus.